The Role Played by Public Universities in Mitigating the Coronavirus Catastrophe in Brazil: Solidarity, Research and Support to Local Governments Facing the Health Crisis - Arrais, Cristiano Alencar; Corcioli, Graciella; Medina, Gabriel da Silva (Frontiers in Sociology, 2021)
This study aims to assess the impacts of the Covid-19 pandemic in Brazil and how it has been dealt with by both the government and in civilian society. To this end, we examine the Brazilian public health system and the measures taken by the Bolsonaro Government that led to Brazil being ranked second in overall Covid-19 infections in the world through August 2020. In the absence of national leadership facing the Covid-19 health crisis, we list a set of science-based initiatives promoted by Brazilian public universities in connection with local governments, NGOs and communities as a means of mitigating the consequences and spread of the pandemic. This study is based on the consultation of institutional material published by universities summarizing their research and outreach initiatives. Results reveal that university initiatives included: 1) Alerts to society on the risks of the pandemic, with an emphasis on establishing observatories that assisted local governments and civilian society in understanding the evolution of the disease, as well as in implementing measures for its prevention; 2) Direct assistance to local communities, with emphases on the addition of beds in university hospitals for treating patients with Covid-19 and on the manufacturing of personal protective equipment and; 3) Research to find solutions to prevent and treat the disease, with emphases on the development of tests for Covid-19, as well as on carrying out phase 3 vaccine trials. Through these measures, Brazilian public Federal Universities played a key role in supporting both civilian society and local governments in mitigating the impacts of the pandemic